UJI MIKROBIOLOGIS BEBERAPA PRODUK KECAP MANIS PRODUKSI LOKAL YANG BEREDAR DI BEBERAPA PASAR KOTA PADANG - Deswita, Fitri; Fifendy, Mades; Nurmiati, Nurmiati (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ Soy bean is a fermented vegetable or animal materials to enhance the flavor of food End the end is a common type of soy sauce on the market is the result of domestic industry, which uses the basic ingredients of soy sauce that is incompatible with products marketed even using basic materials that are inappropriate, improper manufacturing processes, the use of water who does not clean as well as the addition of chemicals dyes and preservatives. The purpose of this study to determine the presence of Fungus and bacteria Coliform and E. coli in the production of soy sauce on some outstanding local market Padang. This study is a descriptive survey of the city of Padang soy sauce production. The study was conducted in the laboratory of Microbiology at the University of Andalas Padang July to August 2013. Sampling was done through a survey in seven markets in the city field and earned four brands of soy sauce production Padang. Of the four brands of soy sauce samples were obtained observed two genera Aspergillus and Penicillium molds which allegedly include the type of Aspergillus niger, Aspergillus flavus, Penicillium citrinum and Penecillium chrysogenum, as well as Coliform bacteria group. Concluded that local production of soy sauce circulating in the city of Padang is microbiologically have found any bad quality because mold and bacteria.Â